1983
DOI: 10.1128/jb.156.2.576-583.1983
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the uvsC, uvsD, uvsE, and mtcA genes in the two pyrimidine dimer excision repair pathways of Deinococcus radiodurans

Abstract: In Deinococcus radiodurans, the genes uvsC, uvsD, uvsE, and mtcA are all involved in the single-strand incision of UV-irradiated DNA, and mutations in at least two of them were required to produce an incisionless strain. One mutation must be in mtcA and one in uvsC, uvsD, or uvsE. Strains carrying single mutations in any one of the genes can incise DNA to the same extent as the wild-type strain. Neither the presence of EDTA nor the absence of protein synthesis affected the incision step. Strains deficient in D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Other studies have indicated the importance of functioning repair systems in determining resistance levels. Strains of Deinococcus radiodurans with impaired abilities to repair UV light-induced DNA damage are less resistant to UV light than are wild-type strains (7). D. radiodurans also is more resistant to heat than are other vegetative cells (2), and heat-induced single-strand breaks of its DNA were shown to be readily repaired (32), suggesting a mechanism for that resistance.…”
mentioning
confidence: 99%
“…Other studies have indicated the importance of functioning repair systems in determining resistance levels. Strains of Deinococcus radiodurans with impaired abilities to repair UV light-induced DNA damage are less resistant to UV light than are wild-type strains (7). D. radiodurans also is more resistant to heat than are other vegetative cells (2), and heat-induced single-strand breaks of its DNA were shown to be readily repaired (32), suggesting a mechanism for that resistance.…”
mentioning
confidence: 99%